Economical evaluation of oil recovery by applying polymer flooding (Research, Society and Development, 2024)
Chemical oil recovery methods are based on mainly three different products, polymers that increase the aqueous phase viscosity, surfactants that reduce interfacial tension between oil and aqueous phases, and alkalis that produce in-situ surfactants when combined with the oil phase acids. Chemical oil recovery methods are often used after waterflooding. Based on this context, this research aims to study the application and comparison of both waterflooding, and Polymer flooding based on a rough economic analysis, such as Net Pay Value (NPV) criteria. To do so, this study used a semisynthetic reservoir model, using characteristics and values like those found in a Brazilian northeast basin. Polymer flooding (PF) was studied at different concentrations, injection rates and sequences through numerical reservoir simulation and was compared to the most profitable scenarios of continuous water flooding (WF). The NPV analysis considered two different prices of barrel of oil, considering the oscillation of international prices. Results showed that polymer flooding improves the amounts of oil recovery at the three used concentrations when compared to WF and that the highest profit was obtained when the lowest PF concentration was injected continuously from the beginning of the reservoir´s productive life. Nevertheless, WF obtained a low difference in terms of NPV when compared to PF´s, but it achieved its highest value one year before PF, leading to a frequent decision regarding to choose between the higher delayed profit or a lower but faster income.